2009
DOI: 10.1109/led.2008.2009235
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative NBTI Study of $\hbox{HfO}_{2}$, $\hbox{HfSiO}_{x}$, and SiON p-MOSFETs Using UF-OTF $I_{\rm DLIN}$ Technique

Abstract: Abstract-The time, temperature, and oxide-field dependence of negative-bias temperature instability is studied in HfO 2 /TiN, HfSiO x /TiN, and SiON/poly-Si p-MOSFETs using ultrafast on-the-fly I DLIN technique capable of providing measured degradation from very short (approximately microseconds) to long stress time. Similar to rapid thermal nitrided oxide (RTNO) SiON, HfO 2 devices show very high temperature-independent degradation at short (submilliseconds) stress time, not observed for plasma nitrided oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…Similar values have been reported. 12,13) These experimental results suggest the validity of our decoupling method.…”
Section: Decoupling Of the Nbti And Hc Components From Hc Degradationsupporting
confidence: 63%
“…Similar values have been reported. 12,13) These experimental results suggest the validity of our decoupling method.…”
Section: Decoupling Of the Nbti And Hc Components From Hc Degradationsupporting
confidence: 63%
“…N EGATIVE bias temperature instability (NBTI) is a crucial reliability concern for silicon oxynitride (SiON) [1] and High-k metal gate (HKMG) [2]- [5] p-MOSFETs. NBTI stress causes positive charge buildup in the gate insulator [6], and variation of device parameters such as threshold voltage ( V T ), transconductance ( g m ), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that NBTI degradation recovers after removal of stress, which has lead to the development of ultrafast measurement (UFM) techniques with microsecond (μs) delay [7], [8], to accurately determine V T due to NBTI. However, till date, UFM has been mostly used for DC NBTI characterization in SiON devices [1], [7]- [9], and except a few cases (as, e.g., in [2]), DC NBTI in HKMG devices was measured using relatively slower methods [3]- [5]. NBTI recovery results in lower V T during AC compared with DC stress [1], [6], [7], [9], and is of interest to switching logic circuits.…”
Section: Introductionmentioning
confidence: 99%
“…NBTI in HKMG devices is governed by the SiON IL, and the HK layer simply acts as a voltage divider [7]. It has been shown that the impact of N is very similar in SiON and HKMG devices [6]. However, it has been recently shown that the SiON [8], [9].…”
Section: Introductionmentioning
confidence: 99%